2020
DOI: 10.1002/eqe.3319
|View full text |Cite|
|
Sign up to set email alerts
|

Fail‐safe optimization of viscous dampers for seismic retrofitting

Abstract: This paper presents a new optimization approach for designing minimum-cost fail-safe distributions of fluid viscous dampers for seismic retrofitting. Failure is modeled as either complete damage of the dampers or partial degradation of the dampers' properties. In general, this leads to optimization problems with large number of constraints. This may result in high computational costs if all the constraints are simultaneously considered during the optimization analysis. Thus, to reduce the computational effort,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
(142 reference statements)
0
10
0
Order By: Relevance
“…This is also true in the case of added viscous damping systems. In recent work by the author, a novel approach to fail-safe design optimization of FVDs was proposed for seismic retrofitting applications, (Pollini, 2020). It was shown that it is possible to develop a computationally efficient framework to design optimal fail-safe damper layouts.…”
Section: Introductionmentioning
confidence: 99%
“…This is also true in the case of added viscous damping systems. In recent work by the author, a novel approach to fail-safe design optimization of FVDs was proposed for seismic retrofitting applications, (Pollini, 2020). It was shown that it is possible to develop a computationally efficient framework to design optimal fail-safe damper layouts.…”
Section: Introductionmentioning
confidence: 99%
“…The fluid viscous dampers were originally developed for military and aerospace industries (Lee and Taylor, 2001). In 1990s, they were found to be also effective in mitigating civil engineering structural vibration, and then gradually be applied to bridges and buildings (De Domenico et al, 2019; Piollini, 2020). Through the flow of internal high-viscosity fluid, massive kinetic energy can be converted into heat and consumed by the viscous damper (Jiao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Stolpe [40] modeled failure as either a complete damage of some predefined number of members or by degradation of the member areas, and concluded that the optimal topology can change drastically even in the situation that only one member is partially degraded. Based on this idea, Pollini [37] performed the fail-safe optimization of viscous dampers.…”
Section: Introductionmentioning
confidence: 99%